Elements of space technology for aerospace engineers - Meyer, Rudolph X. (Academic Press, 1999)
This book is written for an introductory course in space technology. It is intended for senior or graduate level aerospace engineering students and professional engineers seeking a thorough understanding of the aerospace aspects of space systems. As such it focuses on the primary physics and engineering fundamentals necessary to understand and design space based systems. The book does not include the basics of spacecraft electronics, because this is covered in many systems and electronics books and is typically covered in follow-up courses. * Derived from the author's thirty years of experience in the aerospace industry and several years of university teaching experience * More than 130 illustrations * Advanced subjects and problems indicated by asterisks(*)allow the reader and the instructor to omit topics without losing continuity * All chapters correspond to the engineering subdivisions typically found in the aerospace industry * Includes United States and international technologies * Extensive appendix of important data, not easily located in other sources * The book does not include the basics of spacecraft electronics.